Supplementary Motor Area Syndrome in Neurosurgical Practice - Mohammad Hamza Bajwa; Zunaira Pathan; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2026)
Supplementary motor area (SMA) syndrome is a distinct clinical entity observed following surgery of the medial frontal cortex particularly in procedures targetting intraaxial lesions and epileptogenic zones. Characterized by transient, contralateral hemiparesis and, with dominant hemisphere involvement and speech initiation deficits, SMA syndrome presents a significant but reversible postoperative challenge. With the integration of advanced neuroimaging and intraoperative neural tract mapping techniques, our understanding of neuroplasticity in the clinical trajectory and recovery following SMA syndrome has substantially progressed. This review aims to synthesize recent, high-impact studies in the context of brain tumour and epilepsy surgery outlining contemporary insights into SMA function, surgical planning and recovery mechanisms. We contextualize these developments in the light of the foundational work of Laplane et al. (1977), who first characterized the syndrome and explore novel findings on the role of the frontal aslant tract (FAT) in SMA connectivity. The aim is to provide neurosurgeons and neuroscientists with an evidence-based understanding of SMA syndrome and highlight implications for improving functional outcomes in neuro-oncological and epilepsy surgery.